High-intensity interval training reduces neutrophil-to-lymphocyte ratio in persons with multiple sclerosis during inpatient rehabilitation. (June 2021) - Joisten, Niklas; Proschinger, Sebastian; Rademacher, Annette; Schenk, Alexander; Bloch, Wilhelm; Warnke, Clemens; Gonzenbach, Roman; Kool, Jan; Bansi, Jens; Zimmer, Philipp
In persons with multiple sclerosis (PwMS), the neutrophil-to-lymphocyte ratio (NLR) is associated with disability status, symptomatology and disease activity. High-intensity interval training (HIIT) improves many symptoms in PwMS and may positively influence disease progression. Here, we present results from a randomized controlled trial during inpatient rehabilitation on immediate (single bout) and training (3-week intervention) effects of HIIT versus moderate continuous training on NLR and related cellular inflammation markers. Only HIIT reduced the NLR over the 3-week intervention period. These training effects might be due to repetitive inflammatory states with compensatory anti-inflammatory counterbalancing after each HIIT session.